Analyzing the Relationship between Renewable Energy Sources, Economic Growth and Energy Consumption in Greece - Huseynli, Bahman (International Journal of Energy Economics and Policy, 2024)
Renewable energy sources are one of the important economic factors of today. Energy resources have a great place for economic growth. There are many types of renewable energy sources, each of which is one of the indispensable elements for the development and development of countries. In this study, which measures the importance of energy consumption within the scope of economic growth and renewable energy, the effects of renewable energy sources and economic growth on energy consumption are investigated. In the study, the relationship between renewable energy sources, economic growth and energy consumption was examined by making panel cointegration analysis for Greece between 1997-2015. According to the results of the analysis, the panel data model established is significant at the 95% level. The independent factors explain 78% of the dependent variable's variation, according to R2. Energy consumption and renewable energy consumption were negatively correlated. A significant and positive relationship was found between economic growth and energy consumption at the 95% confidence level. An 1% increase in economic growth will increase energy consumption by about 15%. This result obtained because of the estimation also supports the theoretical expectation.